ARTIFICIAL INTELLIGENCE FOR BANKING DEVELOPMENT (European Journal of Economics, Finance and Business Development, 2025)
The article addresses the growth and adoption of artificial intelligence (AI) in the financial sector. It explores the definitions of AI, its types, key technologies, and major trends in their evolution. The article also examines the application of AI across various segments of the financial market, the conditions fostering the development of AI technologies, and potential risks associated with their implementation by financial institutions. Special attention is given to global trends in AI regulation, including existing standards, best practices, and approaches to ensuring the security and ethical use of these technologies. The article emphasizes the importance of adapting to new conditions created by AI-driven innovations and highlights the need for financial organizations to develop strategies that support the effective and safe application of these technologies.